Wind power integration : connection and system operational aspects - Fox, Brendan (IET power and energy series, 2007)
The rapid growth of wind power and the implications of this on future power system planning, operation and control has become an even greater challenge in today's liberated electricity market conditions. This essential new book examines the main problems of wind power integration and guides the reader through a number of the most recent solutions based on current research and operational experience of wind power integration.